Dyslexia in context : research, policy and practice - Reid, Gavin, 1950-; Fawcett, Angela; British Dyslexia Association (London ; Philadelphia : Whurr Publishers, 2004)
This book highlights the most recent developments in the area of research, policy and practice. All the authors are well known in the field of dyslexia and they will offer significant contributions at the forthcoming BDA conference' Dyslexia: the dividends from research to policy and practice' to be held at Warwick University in March 2004.
'Contributions at the BDA conference'Dyslexia: the dividends from research to policy and practice' at Warwick University in March 2004'--Page 4 of cover.
Includes bibliographical references and index.
Print version record.
Keywords: Dyslexia -- Congresses; Electronic books